Hope In The Age Of Innocence Novel By Edith Wharton's (1920):An Individual Psychological Approach - Permadi, Aditya Wahyu; , Dr. Phil. Dewi Candraningrum, M.Ed; , Dr. Abdillah Nugroho, M. Hum (2015)
This research paper aims at knowing hope of Newland Archer reflected in The Age of Innocence novel by Edith Wharton which is analyzed by using individual psychological. The objective of the research is to analyze the novel based on the structural elements of the novel and to analyze the novel based on individual psychological proposed by Alfred Adler. The type of this research is descriptive qualitative. Data of the research are taken from primary and secondary data. The primary data of the research is The Age of Innocence novel. The secondary data of the research are taken from books, other source and website that related to the study. The technique of collecting data are reading novel, classifying the data, identifying the data that can be analyzed, taking note, and browsing to the internet. The method to analyze of this data is descriptive analysis. Based on structural elements of the novel, the Writer delivers a moral message that "hope to fight for love and responsibility". Based on the individual psychological analysis, the author illustrates a psychological phenomenon which an individual should make every effort to cope with the problem of life. The psychological phenomenon is shown by hope and also action by Newland Archer to get his hope. Newland Archer uses his creativity to make a big deal with himself about difficult choices. He also arranges her striving for superiority to provide her inferiority feeling to create fictional finalism.